Identité biologique des artisans moustériens de Kebara (Mont Carmel, Israël) Réflexions sur le concept de néanderthalien au Levant méditerranéen - Anne-Marie Tillier; Baruch Arensburg; Jaroslav Brůžek (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The southern Mediterranean Levant has attracted the attention of the scientific community since the early excavations conducted at the beginning of the 20th century on several sites, which provided a significant sample of Upper Pleistocene hominids. Additional skeletal material, circumscribed geographically and chronologically, raises several questions concerning the biological differences and similarities between the hominid samples represented, and their geographical position at the crossroads of Africa and Eurasia. The excellent state of preservation of the hominid remains enables a new insight into the anatomy of Levantine Middle Palaeolithic populations and provides important data for reconstructing the pattern of human evolution in the Near East. With this in view, re-examination of some skeletal remains recovered at Kebara Cave suggests. that biological differences and similarities may have existed between Neanderthals and Levantine Middle Palaeolithic hominids, strengthening the existence of regional variation.